2011
DOI: 10.1007/s00253-011-3206-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of cell surface characteristics on population dynamics in a sequencing batch yeast reactor treating vegetable oil-containing wastewater

Abstract: Ten yeast strains acquired from different sources and capable of utilizing vegetable oil or related compounds (fatty acid or oleic acid) as sole carbon sources were inoculated into a sequencing batch reactor (SBR) for the treatment of high-strength vegetable oil-containing wastewater. The SBR system stably removed >89% of chemical oxygen demand (COD) and >99% of oil when fed with wastewater containing 15 g/L COD and 10 g/L oil in average. Denaturing gradient gel electrophoresis of polymerase chain reaction-amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The same phenomenon was observed in acetone–butanol–ethanol fermentation wastewater (ABE), where the pH increased with acetic acid consumption [ 20 ]. Lv et al [ 21 ] found that some yeasts had an absorptive effect on oily substances in wastewater. Therefore, the COD and oil content, which decreased significantly in the early stages of wastewater treatment, should be attributed to the absorption on the surface of T. fermentans to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…The same phenomenon was observed in acetone–butanol–ethanol fermentation wastewater (ABE), where the pH increased with acetic acid consumption [ 20 ]. Lv et al [ 21 ] found that some yeasts had an absorptive effect on oily substances in wastewater. Therefore, the COD and oil content, which decreased significantly in the early stages of wastewater treatment, should be attributed to the absorption on the surface of T. fermentans to some extent.…”
Section: Resultsmentioning
confidence: 99%
“…The dominant fungal carbon-degrading genes were mainly derived from Ascomycota such as Aspergillus, which are ubiquitous in natural environments (Schuster et al, 2002) with nutrient degrading abilities (Mannana et al, 2005). Some detected genes were found from Pichia and Candida, which are capable of degrading diverse organic compounds in wastewater (Adav et al, 2007;Hesham et al, 2006;Lv et al, 2011;Zheng et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, clone library analyses revealed that fungal diversity was very low in the full-scale stage, with only Candida tropicalis detected individually. Our previous research showed that inoculated strain Candida tropicalis had the fastest growth rate and organic matter degradation rate of the studied yeast strains, as well as excellent cell emulsification ability and surface hydrophobicity, which made it the dominant strain in oil-heavy polluted wastewater [22]. From the bacterial 16S rRNA gene clone library of sludge samples from the full-scale system, 72 clones were selected and grouped into two OTUs.…”
Section: Composition Of Eukarya and Bacteria In The Pilot And Full-scmentioning
confidence: 99%
“…Yarrowia lipolytica strain (CGMCC 2.1207) is purchased from the China General Microbiological Culture Collection Center (CGMCC), who was clearly identified by CGMCC and studied further by Lv, W.Z. [22]. Pichia anomala (CGMCC 2.4177) strain was isolated from oily soil samples collected from Jidong Oilfield in Hebei Province, China, and identified by analysis of 18S and 26S ribosomal DNA sequences [23].…”
Section: Yeast Strains and Cultivationmentioning
confidence: 99%